2013
DOI: 10.1007/s10897-013-9594-2
|View full text |Cite
|
Sign up to set email alerts
|

“Nothing is Absolute in Life”: Understanding Uncertainty in the Context of Psychiatric Genetic Counseling from the Perspective of those with Serious Mental Illness

Abstract: No genetic tests are currently clinically available for serious mental illnesses such as schizophrenia and bipolar disorder. Rather, the full spectrum of genetic variants that confer susceptibility remain unknown, and estimates of probability of condition recurrence typically have the form of ranges rather than single absolute numbers. Genetic counselors have been shown to feel that the information that can be provided for patients with serious mental illness could be more confusing than helpful. However, how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…These outcomes have been reported by previous studies into the provision of genetic counselling for mental health in Canada (Austin and Honer 2007; Austin and Honer 2008: Hippman et al 2013). Recently, Inglis et al (2015) utilized the Genetic Counselling Outcome Scale (GCOS) (McAllister et al 2011) to assess specialist genetic counselling provision, with individuals and their family members reporting a significant increase in feelings of empowerment one month post genetic counselling.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…These outcomes have been reported by previous studies into the provision of genetic counselling for mental health in Canada (Austin and Honer 2007; Austin and Honer 2008: Hippman et al 2013). Recently, Inglis et al (2015) utilized the Genetic Counselling Outcome Scale (GCOS) (McAllister et al 2011) to assess specialist genetic counselling provision, with individuals and their family members reporting a significant increase in feelings of empowerment one month post genetic counselling.…”
Section: Discussionsupporting
confidence: 79%
“…Studies have highlighted the benefits of providing education about aetiology (DeLisi and Bertisch 2006; Austin and Honer 2008) for affected individuals and their families by improving knowledge, alleviating anxiety and reducing uncertainty of risk for those with a heightened fear of developing a mental illness (Phillips et al 2002; Austin and Honer 2007; Hippman et al 2013). For instance, Rusch et al (2010) emphasize the importance of discussing causes holistically, where understanding genetic and environmental aspects of psychiatric illness is likely to reduce guilt and self-blame.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from the perspective of patients with psychiatric disorders, the uncertainty associated with psychiatric genetic counseling does not significantly detract from its value. In a survey of individuals with a diagnosed psychiatric disorder who received psychiatric genetic counseling, 52% reported that they had expected the uncertainty (Hippman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic counseling that refines clients’ understanding of BPD etiology and related family risk may help patients manage uncertainty [34] and worry, and facilitate coping and adaptation.…”
Section: Discussionmentioning
confidence: 99%